POLITICAL COMPONENT IN THE CONFLICTIZATION OF INTERCONFESSIONAL RELATIONS IN UKRAINE - Obushnyi, Mykola (Київський національний університет імені Тараса Шевченка, 2019)
The article identifies the place and role of the political component in the conflictization of interconfessional relations in Ukraine by taking into consideration that the network of religious organizations in our country is one of the largest on the European continent. Particular attention is paid to the analysis of the political component in the conflictization of interconfessional relations in Ukrainian Orthodoxy. During more than thousand years the Orthodoxy, despite the conflicts between the churches and their believers in past and present is still the most widespread Christian confession in Ukraine. Moreover, it saved a tendency to the inner unity, including creation of the Local Orthodox Church of Ukraine (OCU). Obtaining by the Orthodox Church of Ukraine on January 6, 2019 from the Ecumenical Patriarchate the Thomas was an important step in founding of independent and competent national church. This is also evidenced by the fact that during the first year of existing of the OCU the number of its parishes increase up to 7,000, not less important is the fact that three churches: The Ecumenical Patriarchate of Constantinople, the Hellenic Church and the Patriarchate of Alexandria recognized the OCU and this already testifies its international acceptance as the part of Orthodoxy.Undoubtedly, the Russian occupation of Crimea and Putin's war in Donbas and the support of these shameful actions by the Russian Orthodox Church (ROC) and its Ukrainian branch, the Ukrainian Orthodox Church of the Moscow Patriarchate (UOC MP) served to the political choices and self-identification of a big part of Ukrainian believers and it gives hope for the gradual stabilization (deconflictization) of interconfessional relations in the Ukrainian Orthodoxy.

У статті визначено місце і роль політичної складової у конфліктизації міжконфесійних відносин в Україні, з урахуванням того, що мережа релігійних організацій у державі є однією з найчисельніших на європейському континенті. Особлива увага приділена аналізу політичної складової у конфліктизації міжконфесійних відносин в українському православ’ї. Православ’я ось уже понад тисячу років, незважаючи на історичні та нинішні роз’єднання в середовищі церкви та вірян, і сьогодні залишається найпоширенішою християнською конфесією на українських землях. Понад те, вона зберегла тенденцію до єдності в складі єдиної помісної церкви, що знайшло вияв у створенні єдиної помісної Православної Церкви України. Отримання Томосу (6 січня 2019 р.) від Вселенської Патріархії Православною церквою України є важливим кроком на цьому шляху. Свідченням цього є також і той факт, що упродовж одного ріку функціонування ПЦУ кількість її парафій збільшилася до 7000. Важливим є те, що три православні церкви: Вселенський (Константинопольcький) патріархат, Елладська церква і Александрійський патріархат офіційно визнали її, а це вже свідчить про міжнародну довіру з боку світового православ’я.Безсумнівно, російська окупація Криму та розв’язання путінською Росією війни на Донбасі та підтримка цих ганебних акцій Російською Православною Церквою (РПЦ) та її українською структурою – Українською Православною Церквою Московського Патріархату (УПЦ МП) сприяли політичному вибору та самоідентифікації православних віруючих України, а це вселяє надію на поступову стабілізацію (деконфліктизацію) міжконфесійних відносин у середовищі українського православ’я.
ПОЛІТИЧНА СКЛАДОВА У КОНФЛІКТИЗАЦІЇ МІЖКОНФЕСІЙНИХ ВІДНОСИН В УКРАЇНІ
Keywords: interconfessional relations; conflictization; deconflictization; interonfessional dialogue; the interaction of politics and religion; religious network; religious organization; міжконфесійні відносини; конфліктизація; деконфліктизація; міжконфесійний діалог; взаємодія політики та релігії; релігійна мережа; релігійна організація